2014
DOI: 10.1254/jphs.14r03cr
|View full text |Cite
|
Sign up to set email alerts
|

The Cardiovascular Actions of DOPA Mediated by the Gene Product of ocular albinism 1

Abstract: Abstract. l-3,4-Dihydroxyphenylalanine (DOPA) is the metabolic precursor of dopamine, and the single most effective agent in the treatment of Parkinson's disease. One problem with DOPA therapy for Parkinson's disease is its cardiovascular side effects including hypotension and syncope, the underlying mechanisms of which are largely unknown. We proposed that DOPA is a neurotransmitter in the central nervous system, but specific receptors for DOPA had not been identified. Recently, the gene product of ocular alb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 39 publications
0
13
0
Order By: Relevance
“…Emerging studies, however, indicate that certain intracellular membranes may serve as alternate destinations or even the preferred location for a number of GPCRs where they may couple to different signalling systems and exhibit distinct patterns of subcellular distribution (Irannejad et al ., , ; Jong et al ., ; Branco and Allen, ; Calebiro et al ., ; Campden et al ., ; Joyal et al ., ). One example of an exclusively intracellular GPCR is that of the ocular albinism I (OA1) GPCR, GPR143 (Goshima et al ., ; De Filippo et al ., ). GPR143 localize to melanosomes and late endosomes/lysosomes in pigmented and non‐pigmented cells, where they appear to act as ‘sensors’ regulating organelle biogenesis and maturation (Schiaffino et al ., ; d'Addio et al ., ; Samaraweera et al ., ).…”
Section: Intracellular Gpcrsmentioning
confidence: 99%
“…Emerging studies, however, indicate that certain intracellular membranes may serve as alternate destinations or even the preferred location for a number of GPCRs where they may couple to different signalling systems and exhibit distinct patterns of subcellular distribution (Irannejad et al ., , ; Jong et al ., ; Branco and Allen, ; Calebiro et al ., ; Campden et al ., ; Joyal et al ., ). One example of an exclusively intracellular GPCR is that of the ocular albinism I (OA1) GPCR, GPR143 (Goshima et al ., ; De Filippo et al ., ). GPR143 localize to melanosomes and late endosomes/lysosomes in pigmented and non‐pigmented cells, where they appear to act as ‘sensors’ regulating organelle biogenesis and maturation (Schiaffino et al ., ; d'Addio et al ., ; Samaraweera et al ., ).…”
Section: Intracellular Gpcrsmentioning
confidence: 99%
“…Certain intracellular membranes may even serve as alternate destinations or even the preferred location for a number of GPCRs where they may couple to different signaling systems and exhibit distinct patterns of subcellular distribution (38). Some of the first examples of intracellular GPCRs include the ocular albinism I (OA1) GPCR, or GPR143 (9, 10) which localizes to melanosomes and late endosomes/lysosomes in pigmented and non-pigmented cells (11); the prostaglandin EP 3 and EP 4 receptors which signal from nuclei in many tissues including the brain (12), and mGlu 5 receptors which also signals from neuronal nuclei as well as from ER membranes (13). In addition, GPCRs have been found on vesicles, mitochondria (14), outer and inner nuclear membranes (3, 8, 15, 16), and even within the nucleoplasm on nuclear bodies and/or nuclear invaginations (1719).…”
Section: Introductionmentioning
confidence: 99%
“…Goshima and co-workers, who performed microinjections into the nucleus tractus solitarius (NTS) to investigate cardiovascular actions of L-DOPA through GPR143, could not exclude that dopamine converted from L-DOPA in non-neuronal tissues would be also able to exert cardiovascular and/or renal actions through β-adrenergic receptor and dopamine receptors D 1 R and D 2 R ( Goshima et al, 2014 ). It was shown that D 1 R activity in vascular smooth muscle is associated with vasodilatation ( Kohli, 1990 ).…”
Section: Gpr143 Functionmentioning
confidence: 99%